Synergistic Aging Effect of Polyether Polyurethane Coatings - Wang, H.Y.; Wang, Y.Z.; Jiang, Y.F.; Li, X.S. (Asian Journal of Chemistry, 2013)
The pure polyether polyurethane (ETPU) and the modified polyether polyurethane (M-ETPU) coatings containing composite additives were prepared by spin-coating technique. The accelerated aging tests of the coatings exposed to constant UV radiation with an ozone atmosphere were carried out by using a self-designed aging equipment. The aging resistance properties of the coatings were evaluated by UV-visible spectra, Fourier transform infrared spectra, yellowness index, photo-oxidation index and carbonyl index analysis. The results show that the ozone and ultraviolet initiate autoxidation of urethane bridge in the polymer chain to quinone-imide structure and trigger formation of hydroperoxides and new carbonyl species. The aging of the coatings increases with incremental exposure time, the aging of M-ETPU coating is much lower than that of ETPU coating at the same condition. There is distinct synergistic aging effect when the yellowness index, the photo-oxidation index and the carbonyl index is used as evaluation index, respectively.